Perilaku Keuangan Driver Ojek Online di Kota Surakarta Dalam Perspektif Akuntansi Keperilakuan - Sanusi Dwiky Sanyoto; Rispantyo Rispantyo (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This research is based on the unstable and unpredictable nature of online motorcycle taxi drivers' income, which requires flexible financial management. In this situation, financial decisions are influenced by both rational considerations and psychological elements. This study aims to analyze how income is managed and expenditures are distributed, identify the impact of behavioral biases on financial decision-making, and understand how online motorcycle taxi drivers in Surakarta record and control their personal finances through a behavioral accounting perspective. This study uses a qualitative approach through in-depth interviews with online motorcycle taxi drivers as a source of information. Data are processed descriptively by linking field research findings with behavioral accounting concepts and behavioral bias theory. The results indicate that income management is carried out adaptively, prioritizing operational expenses and daily needs. Mental accounting factors, such as present bias, loss aversion, anchoring, and overconfidence, influence the financial decision-making process. Financial recording activities are carried out in a simple manner as an effort to control themselves. This research confirms that drivers' financial behavior does not strictly follow economic logic, making a behavioral accounting perspective relevant to explaining this phenomenon